AN ERROR ANALYSIS IN WRITING THE SENTENCE OF SIMPLE PAST TENSE ON ENGLISH SUBJECT - Sari, Eka Resty Novieta (Universitas Nusantara PGRI Kediri, 2019)
This research was conducted to determine the types of errors had been made by students in writing the sentence of simple past tense in English subjects. The low level of student understanding of simple past tense material is one of the reasons which influence the mistakes in making the sentence of simple past tense. It could be proven through the results of the pra-test, where four types of errors were found, namely (1) Error using verb suffix (-ed, -d) in regular verb words, (2) Error using simple verb forms past tense irregular verb, (3) Error using the help word in negative sentences, (4) Error Using To be. However, after the teaching and learning process was carried out, the error was reduced, including in the use of the suffix on the verb (-ed, -d) in the regular verb of the previous 15 students had been reduced to 5 people. While errors in the use of simple past tense verb forms (irregular verb) from the previous 14 students become 3 students. Furthermore, errors in the use of the help word in negative sentences were carried out by 13 students into 2 students. Then errors in use to be in the simple past tense carried out by 15 people decreased to 2 people.Keywords: Simple Past Tense, Error Analysis